Consumption Behaviors and Awareness of fast food among the Young Generation: An Empirical Study on Hostel Living Students in Kathmandu Valley - Regmi, Mithu (Namuna Academic Journal, 2023)
This research aims to study the fast-food habits of the young generation, who are staying in hostels. It intends to study the role of parents and advertisement regarding on consumption behaviours and awareness of fast food. Food is considered as an important representation of all social groups. Although the trend has changed, its impacts exist on the whole society, whether it belongs to the lower middle class or elite class. Fast food is considered as easy to make and ready to eat, so in present days, the young generation is attracted to fast food outlets as hanging places with friends in search of new tastes and places. Hostel life is entirely different and independent from the in-home, especially in terms of food eating. Keeping this view in mind, this research was conducted in two hostels in Kathmandu metropolitan city. This is qualitative research. Based on my research I argue that there is a link between food, parents’ roles, behaviors pattern of hostellers, and advertising.